In-service diagnostics for wire-bond lift-off and solder fatigue of power semiconductor packages - Eleffendi, Mohd Amir; Johnson, Christopher Mark (IEEE, 2017)
Wire-bond lift-off and Solder fatigue are degradation mechanisms that dominate the lifetime of power semiconductor packages. Although their lifetime is commonly estimated at the design stage, based on mission profiles and Physics-of-Failure models, there are many uncertainties associated with such lifetime estimates, emerging, for example, from model calibration errors, manufacturing tolerances, etc. These uncertainties, combined with the diverse working environments of power semiconductor packages result in inaccurate lifetime estimates. This paper presents an approach for estimating the extent of degradation in power semiconductor packages based on online monitoring of key parameters of the semiconductor, namely, the thermal resistance Rthja and the electrical resistance RCE. Using these two parameters, solder fatigue and wire-bond lift-off can be detected during normal converter operation. In order to estimate these two parameters, two techniques are introduced: a residual obtained from a Kalman filter which estimates the change in the thermal resistance Rthja and a Recursive Least-Squares (RLS) algorithm which is used to estimate the electrical resistance. Both methods are implemented online and validated experimentally.